2018
DOI: 10.1177/1533033818791792
|View full text |Cite
|
Sign up to set email alerts
|

Navigation Systems for Treatment Planning and Execution of Percutaneous Irreversible Electroporation

Abstract: The application of navigational systems has the potential to improve percutaneous interventions. The accuracy of ablation probe placement can be increased and radiation doses reduced. Two different types of systems can be distinguished, tracking systems and robotic systems. This review gives an overview of navigation devices for clinical application and summarizes first findings in the implementation of navigation in percutaneous interventions using irreversible electroporation. Because of the high number of n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…However, we observed a range of responses we classified as low, average, and high responses. In clinical applications of IRE, computational modeling is used to map and plan treatment for each individual patient, leading to improved ablation zone coverage [[49], [50], [51], [52]]. We did not model electrode placement in the mouse studies due to experimental limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed a range of responses we classified as low, average, and high responses. In clinical applications of IRE, computational modeling is used to map and plan treatment for each individual patient, leading to improved ablation zone coverage [[49], [50], [51], [52]]. We did not model electrode placement in the mouse studies due to experimental limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The key message of this study is the necessity of navigation solutions with respect to reproducibility in percutaneous, laparoscopic, and open interventions [34]. Another report investigating the accuracy between guided and manual probe placement shows a significant advantage for the guided approach [35]. Martin et al [36] discuss the advantages of computer assistance in the placement of single needles during a liver phantom study demonstrating that 95% of the participants were able to hit the center of the tumor using the computer-assisted approach compared to 65% with ultrasound (US) only.…”
Section: Computer-assisted Needle Guidancementioning
confidence: 87%
“…Previous publications have shown that the use of a stereotactic CT-based navigation systems in placing applicators for MWA and RFA is safe and accurate 6 , 7 , 10 12 . Furthermore, several studies have shown the use of stereotactic navigation in IRE treatment with good results 13 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proven the safety and efficacy of stereotactic CT-guidance for placement of single applicators in RFA and MWA 10 13 .…”
Section: Introductionmentioning
confidence: 99%